The Three Seas Initiative: regional cooperation or a military project for new Europe? - Juri, Luka (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2024)
The study examines the Three Seas Initiative as a geopolitical and geoeconomic platform in Central and Eastern Europe and asks whether its primary purpose is economic development or a military strategy. Using a comparative analysis of the economic and geopolitical dimensions, it concludes that while the Three Seas Initiative projects offer economic benefits, they primarily serve strategic military objectives. It emphasizes the role of Three Seas Initiative in strengthening NATO capabilities and its alignment with U. S. geopolitical priorities.
Keywords: Central Europe; Eastern Europe; geopolitics; geopolitika; military infrastructure; NATO; Pobuda treh morij; political geography; politična geografija; Rusija; Russia; Srednja Evropa; Three Seas Initiative; United States of America; vojaška infrastruktura; Vzhodna Evropa; Združene države Amerike